Lupus Myositis with Normal Creatinine Kinase Levels Following Adalimumab Use in a Rheumatoid Arthritis Patient - Hani ALMOALLIM,; Ahlam ALMASARI,; Hadeel KHADAWARDI1, (Archives of Rheumatology, 2011)
We report a rare case of histopathologically confirmed lupus myositis that developed in a 32-year-old female with seropositive rheumatoid arthritis that had been treated with adalimumab for one year. She had demonstrated excellent response to her arthritis initially but then developed profound muscle weakness with a conversion of her antinuclear antibody and anti-double stranded DNA from negative to strongly positive. Her creatinine kinase levels remained normal. She responded well to high-dose steroid therapy and rituximab.